FAKTOR FUNDAMENTAL SEBAGAI PENENTU INITIAL RETURN - Rivandi, Muhammad (Jurnal Benefita, 2017)
Initial public offerings (IPO) are a strategy that can be implemented in meeting the needs of corporate fund. This study aims to examine the effect of Current Ratio, Debt Equity Ratio and Return On Equity on the initial Return. The samples of this study are thirty-three companies listed in Indonesia Stock Exchange (IDX) selected by using purposive sampling method. Data analysis method used is multiple linear regression model. Based on the hypothesis tested proves that the Current Ratio, and Debt Equity Ratio significantly no effect on Initial Return, meanwhile Return On Equity have had The positive significant effect  on Initial ReturnInitial public offerings (IPO) merupakan strategi yang dapat diimplementasikan dalam memenuhi kebutuhan dana. Penelitian ini bertujuan untuk menguji pengaruh Current Ratio, Debt Equity Ratio dan Return On Equity terhadap Initial Return. Sampel dalam penelitian ini adalah 33 perusahaan yang terdaftar di Bursa Efek Indonesia yang dipilih dengan menggunakan metode regresi linear Berganda. Berdasarkan hipotesis yang telah diuji bahwa Current Ratio, dan Debt Equity Ratio tidak berpengaruh terhadap Initial Return, sedangkan Return On Equity berpengaruh positif signifikan terhadap Initial Return